IMPLEMENTASI PROGRAM PEMBERDAYAAN EKONOMI KELUARGA MISKIN (PEKM) DI KECAMATAN BANGUNTAPAN KABUPATEN BANTUL - , HERIZA SYAFANI; , Dr. Nunuk Dwi Retnandari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Poor Families Economic Empowerment Programme ( PEKM ) is one of policy efforts of the Government of Bantul regency for poverty alleviation and community . Research conducted in Banguntapan - Bantul district is intended to determine how the performance of the implementation of the program in improving the ability of families PEKM poor / less able to perform economically productive activities facilitated by channeling capital revolving fund PEKM and mentoring . There are two questions as a research problem that will be answered through this research , namely : ( 1 ) how the program PEKM implementation process ( 2 ) how the performance of the implementation program Banguntapan - PEKM in Bantul district , and ( 3 ) the factors that influence the performance of the implementation of the program PEKM in the Bantul district Banguntapan. The method used is descriptive method with qualitative approach . Furthermore, in this study, the research object is the target group PEKM, PEKM group members who come from poor families ( underprivileged ) and poor families ( prosperous ) who received revolving loan fund capital PEKM both regular and revolving as well as the reward fund . The data obtained are primary and secondary data on monitoring / observation , in-depth interviews , Focus Group Discussion ( FGD ) and documentation , as well as supporting data from literature or literature based on the variables and indicators that have been determined , so the data were then verified and reduced to analyzed through data interpretation and analysis of empirical data in accordance with the focus / theme of the study , so the results of these analyzes are expected to be found to answer the research question , of course, to see a trend emerging phenomenon of the relationship between variables. From the analysis , it was concluded : ( 1 ) Program is an innovative PEKM Bantul local government to empower the poor toward a prosperous community with funds from the budget , (2 ) the performance of the implementation of a program PEKM capital revolving fund loan facilitation and assistance efforts with the principles of socio - economic empowerment not utilized properly , this is due to the lack of guidance by the management group PEKM which also serves as the implementor of programs and companion ( agents of change ) member of the group , but it is also due to lack of coaching field officers and field officers cadre / PPKBD due to the burden of such a large task and tend concentrated on the issue of family planning , (3 ) the implementation of the program has not been optimal performance Banguntapan PEKM in the district due to a lack of knowledge , skills , awareness and motivation of the group members PEKM in starting his business as one that benefits PEKM program objectives not fully achieved , (4 ) but some members of the group have also felt the impact of the resulting program , especially from a reward fund fixed capital group , as well as revolving capital utilization is the growing income group members to help meet their family needs .